The Jesuit series. - Dimler, G. Richard, 1931-; Daly, Peter M. (Peter Maurice) (Corpus librorum emblematum., 2000)
This bibliography encompasses all extant books of emblems, and books dealing with the theory and practice of emblematics written by members of The Society of Jesus. Translations and adaptations of Jesuit works in all languages are also included.